Interactions between suspension characteristics and physicochemical properties of silver and copper oxide nanoparticles: A case study for optimizing nanoparticle stock suspensions using a central composite design. (April 2015) - Son, Jino; Vavra, Janna; Li, Yusong; Seymour, Megan; Forbes, Valery
Highlights: Effects of sonication on AgNP and CuONP properties were investigated. A central composite design was used to optimize the preparation of AgNP and CuONP stock suspensions. All properties of NPs were sensitive to sonication time and concentration. All properties of NPs could be predicted by sonication time and concentration. Abstract: The preparation of a stable nanoparticle stock suspension is the first step in nanotoxicological studies, but how different preparation methods influence the physicochemical properties of nanoparticles in a solution, even in Milli-Q water, is often under-appreciated. In this study, a systematic approach using a central composite design (CCD) was employed to investigate the effects of sonication time and suspension concentration on the physicochemical properties (i.e. hydrodynamic diameter, zeta potential and ion dissolution) of silver (Ag) and copper oxide (CuO) nanoparticles (NPs) and to identify optimal conditions for suspension preparation in Milli-Q water; defined as giving the smallest particle sizes, highest suspension stability and lowest ion dissolution. Indeed, all the physicochemical properties of AgNPs and CuONPs varied dramatically depending on how the stock suspensions were prepared and differed profoundly between nanoparticle types, indicating the importance of suspension preparation. Moreover, the physicochemical properties of AgNPs and CuONPs, at least in simple media (Milli-Q water), behaved in predictable ways as a function of sonication time and suspension concentration, confirming the validity of our models. Overall, the approach allows systematic assessment of the influence of various factors on key properties of nanoparticle suspensions, which will facilitate optimization of the preparation of nanoparticle stock suspensions and improve the reproducibility of nanotoxicological results. We recommend that further attention be given to details of stock suspension preparation before conducting nanotoxicological studies as these can have an important influence on the behavior and subsequent toxicity of nanoparticles.